Platelet Cyclooxygenase Inhibition by Low-Dose Aspirin Is Not Reflected Consistently by Platelet Function Assays : Implications for Aspirin Resistance - SANTILLI, Francesca; ROCCA, Bianca; DAVI, Giovanni; PATRONO, Carlo; DE CRISTOFARO, Raimondo; LATTANZIO, Stefano; PIETRANGELO, Laura; HABIB, Aida; PETTINELLA, Caterina; RECCHIUTI, Antonio; FERRANTE, Elisabetta; CIABATTONI, Giovanni (Journal of the American College of Cardiology, 2009)
This study was conducted to assess the thromboxane (TX) dependence of biochemical and functional indexes used to monitor the effect of low-dose aspirin. Functional assays of the antiplatelet effects of low-dose aspirin variably reflect the TX-dependent component of platelet aggregation. Previous studies of aspirin resistance were typically based on a single determination of platelet aggregation. We assessed the TXB(2) dependence of biochemical and functional indexes, as well as their intersubject and intrasubject variability during administration of the drug and after its withdrawal in 48 healthy volunteers randomized to receive aspirin 100 mg daily for 1 to 8 weeks. Serum TXB(2) was uniformly suppressed by 99% of baseline. Urinary 11-dehydro-TXB(2), arachidonic acid-induced aggregation, and VerifyNow Aspirin (Accumetrics Inc., San Diego, California) showed stable, incomplete inhibition (65%, 80%, and 35%, respectively). Adenosine diphosphate- and collagen-induced aggregation was highly variable and poorly affected by aspirin, with an apparent time-dependent reversal. Inhibition of platelet cyclooxygenase activity was nonlinearly related to inhibition of platelet aggregation. Platelet function largely recovered by day 3 post-aspirin, independently of treatment duration. With any functional assay, occasionally "resistant" subjects were found to be "responders" on previous or subsequent determinations. Platelet cyclooxygenase activity, as reflected by serum TXB(2) levels, is uniformly and persistently suppressed by low-dose aspirin in healthy subjects. However, the effect of aspirin is variably detected by functional assays, potentially leading to misclassification of "responder" as "resistant" phenotypes owing to poor reproducibility of functional measurements. The nonlinearity of the relationship between inhibition of TX production and inhibition of platelet function has important clinical implications.